A Bayesian approach for non-homogeneous gamma degradation processes. Issue 7 (3rd April 2019) - Guida, Maurizio; Postiglione, Fabio; Pulcini, Gianpaolo
ABSTRACT: A Bayesian approach based on the Markov Chain Monte Carlo technique is proposed for the non-homogeneous gamma process with power-law shape function. Vague and informative priors, formalized on some quantities having a "physical" meaning, are provided. Point and interval estimation of process parameters and some functions thereof are developed, as well as prediction on some observable quantities that are useful in defining the maintenance strategy is proposed. Some useful approximations are derived for the conditional and unconditional mean and median of the residual life to reduce computational time. Finally, the proposed approach is applied to a real dataset.